Assessing Aegis Program Transition to an Open-Architecture Model - DeLuca, Paul (RAND Corporation, 2013)
To reduce the costs of maintaining the Aegis system, and to take advantage of rapidly evolving commercial computing technology, the U.S. Navy is moving toward open-architecture software, a common source code library, and commercial, off-the-shelf processors. This report examines the potential benefits of this new model, the pace of upgrades, and the best way for the Navy to maximize the technological and financial benefits.